KEPUTUS$I STRATEGIS INTERIASIONALISASI BISNIS STUDI PT TELEKOMUNIKASI INDONBSIA INTERNATIONAL - , Noor Mahmudah Moorcy ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study is to analyze the strategic choice in the internationalization of PT. Telekomunikasi Indonesia International (Telin) business which covers some aspects which are: motivation on the internationalization of business, choosing the entry strategy in the international market, and the competitiveness strategy in the international market. This research is categorized as qualitative descriptive and the methods used in the analysis are weighted factor analysis, the method of critical variable trade-off by Driscoll and SPACE matrix framework to determine the competitiveness strategy in international market. Based on this study, from five motivation on internationalization of business in accordance to Thomson (2010) which are: access to new market, cost reduction, capitalizing main competencies, risk sharing, and striving competition, the main motivation for Telkom is to capitalize their main competencies: domestic business, sustainability from competition, and complementing domestic business. The selection of entry strategy into international market is not executed based on the staging of indirect export, export, joint venture and wholly owned subsidiary, but it is more following what is reinforced by Driscoll (1995) where the selection of strategy is based on the internal commitment which consider the situation of industry, environment and the company itself by trading-off some variables including control, transfer risk, resource intensity and learning, Delfmann (2008). Initially, Telkom considered the necessity of fully control where the entry strategy into international market should be through wholly owned subsidiary. However, by considering that it is difficult in the international market to get the business target with manageable risk and high volatility on the investment, then Telkom decided that the ownership shouldnât be dominant, and the entry strategy is decided based on âMPTNâ (follow the Money, follow the People, follow the Traffic, and follow the Network). The competitiveness strategy implemented are as follow: Aggressive for Telin Hongkong, Telkomcel Timor Leste, Telin Malaysia, Telin Myanmar and Saudi Arabia